Zein Nanoparticles Loaded with Vitis vinifera L. Grape Pomace Extract: Synthesis and Characterization - Ana Guadalupe Luque-Alcaraz; Jesús Antonio Maldonado-Arriola; Pedro Amado Hernández-Abril; Mario Enrique Álvarez-Ramos; Cynthia Nazareth Hernández-Téllez (Nanomaterials)
This study investigates the synthesis and characterization of zein nanoparticles (ZNp) loaded with grape pomace extract (GPE) from Vitis vinifera L. for applications in controlled release and antioxidant delivery. Grape pomace, a byproduct of the winemaking industry, is rich in bioactive compounds, including phenols and flavonoids, which possess antioxidant properties. To overcome the limitations of these compounds, such as photosensitivity and thermal degradation, they were incorporated into zein nanoparticles using the antisolvent technique. The physicochemical properties of the ZNp-GPE system were thoroughly characterized, including size, morphology, ζ-potential, and total phenol content. Results showed high encapsulation efficiency (89–97%) and favorable loading capacities. Characterization techniques, such as scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and dynamic light scattering (DLS), confirmed that GPE was successfully incorporated into the nanoparticles, thereby enhancing their antioxidant properties. The encapsulation process did not significantly alter the spherical morphology of the nanoparticles, and loading GPE resulted in a decrease in particle size. Total phenol content analysis showed that the ZNp-GPE nanoparticles effectively retained these compounds, confirming their potential as efficient delivery systems for antioxidants. This approach not only provides a method for protecting and enhancing the bioavailability of natural antioxidants but also contributes to the valorization of agricultural waste, promoting sustainability in bio-based industries.